First evidence of chromosomal variation within Chelonoidis chilensis (Testudines: Testudinidae) - Sánchez, Julieta (2015)
Chelonoidis chilensis is an endangered tortoise that inhabits arid regions in Argentina, Bolivia and Paraguay. Blood samples were obtained from wild specimens from the Argentinan distribution range together with samples from specimens of known morphotype but unknown provenance. Cytogenetic analysis using Giemsa staining showed that the diploid chromosome complement was 2n=52 for all twenty-five tortoises analysed. Two different karyomorphs, termed A and B, were identified, with a karyotypic formulae of 7:5:14 and 6:5:15, respectively. G-band analysis suggests that karyomorph B may originate from a chromosomal fission event involving chromosome pair 7 of karyomorph A. In addition, all specimens analysed using Fluorescence In Situ Hybridisation (FISH) with a telomeric probe showed telomeric signals only at the terminal regions of chromosomes. This evidence suggests that the karyotype of C. chilensis does not have telocentric chromosomes, and that interstitial telomeric sequences have not played a major role during the recent chromosomal evolution of this species. Our data agree with recent molecular evidence supporting the existence of one instead several species for the C. chilensis complex. Our data further suggest a possible correlation between chromosomal variation and geographical distribution: karyomorph A is present in tortoises from the Dry Chaco Eco-region, whereas karyomorph B characterises tortoises living in the Monte of Steps and Plains Eco-region. Morphology appears to vary independently of cytomorph variation.